Optimization Studies on Cellulase Production from Bacillus Anthracis and Ochrobactrum Anthropic (YZ1) Isolated from Soil - Duza, Mohammad Badrud; Mastan, S.A. (International Journal of Applied Sciences and Biotechnology, 2015)
The present study was carried out to demonstrate the optimization of growth conditions of bacteria with high cellulase activity. Cellulose degrading bacteria were isolated from soil samples collected from different areas of Guntur district, A.P. The bacteria were isolated using serial dilution and pour plate methods. The isolated bacteria were identified by morphological, biochemical and molecular procedures. The isolated bacterial species were screened for cellulase production in sub-merged fermentation process. The two tested bacterial species showed maximum yield for cellulase production. These two bacteria were identified as Bacillus anthracis and Ochrobactrum anthropi (YZ1). Supplementation of glucose, peptone, tyrosine and EDTA to the fermentation medium is favoured enzyme secretion. The optimum pH and temperature for the activity of crude enzyme was 8 and 45°C, respectively for Ochrobactrum anthropi (YZ1) while for Bacillus anthracis, it was 8 and 4°C, respectively.14% of inoculum level and 96 h of incubation period showed the maximum yield by both the species bacteria for cellulase production. The results of present study indicated that favorable fermentation conditions and the selection of a suitable growth medium played a key role in the production of cellulase from newly isolated Bacillus anthracis and Ochrobactrum anthropi (YZ1).Int J Appl Sci Biotechnol, Vol 3(2): 272-284 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12616